The Civic Side of Diversity: Ambivalence and Belonging at the Neighborhood Level. (March 2019) - Hoekstra, Erin; Gerteis, Joseph
Although diversity has become a cherished ideal for Americans, a growing literature suggests that many are also ambivalent about lived experiences of diversity. Focusing on three historically homogeneous neighborhoods in Atlanta, Minneapolis, and Los Angeles, this paper explores the "civic talk" used to express this ambivalence through interrelated frames of social order and civic engagement. In all three neighborhoods, long–term residents and neighborhood association members speak fluently about race, class, and other forms of diversity in their neighborhoods. Yet when they assess who "belongs" in the neighborhoods, the discussion is coded in civic terms. This framing enables neighborhood association members to act as gatekeepers, wielding civic discourse in ways that reinforce traditional neighborhood boundaries and social hierarchies, while maintaining structural inequalities.